Rad9, a 53BP1 Ortholog of Budding Yeast, Is Insensitive to Spo11-Induced Double-Strand Breaks During Meiosis - Usui, Takehiko; Shinohara, Akira (Frontiers in Cell and Developmental Biology, 2021)
Exogenous double-strand breaks (DSBs) induce a DNA damage response during mitosis as well as meiosis. The DNA damage response is mediated by a cascade involving Mec1/Tel1 (ATR/ATM) and Rad53 (Chk2) kinases. Meiotic cells are programmed to form DSBs for the initiation of meiotic recombination. In budding yeast, Spo11-mediated meiotic DSBs activate Mec1/Tel1, but not Rad53; however, the mechanism underlying the insensitivity of Rad53 to meiotic DSBs remains largely unknown. In this study, we found that meiotic cells activate Rad53 in response to exogenous DSBs and that this activation is dependent on an epigenetic marker, Dot1-dependent histone H3K79 methylation, which becomes a scaffold of an Rad53 mediator, Rad9, an ortholog of 53BP1. In contrast, Rad9 is insensitive to meiotic programmed DSBs. This insensitiveness of Rad9 derives from its inability to bind to the DSBs. Indeed, artificial tethering of Rad9 to the meiotic DSBs activated Rad53. The artificial activation of Rad53 kinase in meiosis decreases the repair of meiotic DSBs. These results suggest that the suppression of Rad53 activation is a key event in initiating a meiotic program that repairs programmed DSBs.